MESENCHYMAL STEM CELLS FROM ADIPOSE TISSUE TO TIGHTEN FACIAL SKIN - Najah, Adilla Syahsiyatun; Haryanto; Fadila, Aghniya Nur Rizka; Wibawa, Alifah Mustari Mukti; Sulasikin, Almaydha Naim; Salsabila, Aulia Putri; Salsabila, Anbar Rania; Luthfi, Cahya Arsya; Raflianti, Desti; Hakim, Elsya Bayduri (Stem Cell Research and Development Center, Universitas Airlangga, 2025)
Skin elasticity is an important aspects of facial care. This study aims to explore the potential of mesenchymal stem cells (MSCs) derived from adipose tissue (adipose-derived stem cells) in facial skin tightening and assess their advantages and limitations in clinical applications. The methods used include literature searches from various officially published online sources as well as analysis of research data regarding the process of isolation, culture, differentiation and clinical applications of ADSCs. The main findings show that adipose-derived stem cells (ADSCs) are able to form new collagen, increase skin elasticity, and repair tissue damage due to aging. The culture process involving isolation of cells from adipose tissue and differentiation of the cells into fibroblasts is essential to exploit the regenerative potential of these cells. Although this technology is promising, this study also identified technical and regulatory challenges that need to be overcome, including patient health criteria, safe ADSc harvest procedures, isolation and culture processes that have a high chance of differentiation and post-application care of ADSc therapy. The significance of these findings is that a better understanding of the mechanism of action of ADSCs can make a positive contribution to the development of beauty therapies that are more effective and safer compared to conventional methods that are often unsatisfactory. Additionally, this approach is expected to provide a long-term solution for individuals who wish to maintain a youthful appearance without the risk of significant side effects. Thus, this research can be a step in integrating stem cell technology in the beauty industry, especially for anti-aging treatments.